PENGEMBANGAN MULTIMEDIA PEMBELAJARAN MEMBACA PADA ANAK USIA DINI - Apriani, Nani; Fadillah, Fadillah; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine multimedia in reading learning activities in early childhood. The focus of this multimedia development research is elaborated to answer several research questions: 1. The design of multimedia reading learning in children aged 5-6 years ?, 2. The use of multimedia reading learning in children aged 5-6 years? 3. Learning outcomes of children reading using multimedia in children aged 5-6 years? The method used in this study is the Borg and Gall development method combined with the Dick and Carey model with 13 research subjects in TK Islamiyah. The stages are research and information collecting, planning, developing preliminary form of product, main field testing, operational product revision, and final product revision. The results of this study found that the learning multimedia design has been tested and validated for early childhood, the use of multimedia learning is arranged based on the needs of children, and the learning outcomes of children using multimedia in the learning process of children are encouraged to face learning activities. Thus multimedia learning in early childhood can help children learn more easily in reading.Â Keywords: Early Childhood, Development, Multimedia, Reading